Professional development for language support in science classrooms: Evaluating effects for elementary school teachers. (January 2022) - Heppt, Birgit; Henschel, Sofie; Hardy, Ilonca; Hettmannsperger-Lippolt, Rosa; Gabler, Katrin; Sontag, Christine; Mannel, Susanne; Stanat, Petra
Abstract: We investigate the effectiveness of professional development (PD) aimed at promoting teachers' language-support skills in elementary school science instruction. In a 2-year quasi-experimental field trial study with 32 teachers in Germany, an intervention group (IG) and a control group (CG) received PD for teaching selected science topics; the IG additionally received PD for language support. Strong treatment effects emerged on teachers' language-support skills and, to a lesser extent, on language support activities in classroom teaching. All teachers gained pedagogical content knowledge and self-efficacy for teaching elementary school science, thus pointing to the effectiveness of the PD. Highlights: We evaluated a professional development program (PD) in a quasi-experimental field trial. The PD included courses on elementary school science topics and on subject-integrated language support. We found strong treatment effects on elementary school teachers' language-support skills. Effects on language-support activities in the classroom were smaller and differed across science topics. For science, positive effects emerged for one out of two topics and for teachers' self-efficacy.